2015
DOI: 10.1002/j.0022-0337.2015.79.1.tb05852.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Calibration of Periodontal Diagnosis and Treatment Planning Among Dental Students at Three Dental Schools

Abstract: Calibration in diagnosis and treatment planning is dificult to achieve due to variations that exist in clinical interpretation. To determine if dental faculty members are consistent in teaching how to diagnose and treat periodontal disease, variations among dental students can be evaluated. A previous study reported high variability in diagnoses and treatment plans of periodontal cases at Indiana University School of Dentistry. This study aimed to build on that one by extending the research to two additional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 18 publications
0
48
3
1
Order By: Relevance
“…Dental practitioners have noticed that there are obvious differences in the presentation of periodontal diseases among patients and have attempted to classify periodontal diseases (4). Classification systems have been developed to aid diagnosis and treatment decisions (5), yet even with these systems in place, considerable disagreements in diagnosis and classification have been reported among dental practitioners when using the 1999 classification of periodontal disease (6,7). These inconsistencies could cause over-or underestimation of the severity and extent of periodontal disease and may lead to inappropriate treatment selection for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dental practitioners have noticed that there are obvious differences in the presentation of periodontal diseases among patients and have attempted to classify periodontal diseases (4). Classification systems have been developed to aid diagnosis and treatment decisions (5), yet even with these systems in place, considerable disagreements in diagnosis and classification have been reported among dental practitioners when using the 1999 classification of periodontal disease (6,7). These inconsistencies could cause over-or underestimation of the severity and extent of periodontal disease and may lead to inappropriate treatment selection for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dental and dental hygiene clinical faculty members often do not provide consistent instruction, especially since most procedures involve clinical judgment 1 15 . These variations of instruction frequently translate into variations of student performance in, for example, the diagnosis and treatment of periodontal conditions 10 . Although the effect of inconsistent instruction is yet unknown, students may experience detrimental effects from the delivery of inconsistent faculty instruction 2 , 7 , 16 18 .…”
mentioning
confidence: 99%
“…On the other hand, studies exploring both diagnostic judgements and treatment decision, although separately, have been conducted on dental students from different dental schools. These studies showed that the diagnostic and treatment agreement between students, both within and between the dental schools, were low (John et al, 2013, Lane et al, 2015. Moreover, 31 clinical instructors also vary in their interpretation of clinical findings, periodontal diagnosis, and treatment planning (Lanning et al, 2005) but on the other hand a substantial agreement could be seen between periodontists when discriminating between patient cases with chronic and aggressive periodontitis (Oshman et al, 2016).…”
Section: Clinical Decision-making In Periodontologymentioning
confidence: 99%
“…Interestingly a substantial number of DSPs stated that they have received insufficient teaching in periodontology. On the other hand, diagnostic variations are common both within and between dental schools (Lane et al, 2015, John et al, 2013. Several factors could be held accountable for this variation.…”
Section: Distinguishing Between Gingivitis and Periodontitismentioning
confidence: 99%
See 1 more Smart Citation